Analysis of the Effect of Job Characteristics, Compensation, Religiosity on Employee Loyalty at Tabassam Farm Mojokerto - Ahmad Sahro Wardi (International Journal of Review Management Business and Entrepreneurship (RMBE), 2021)
The aims of this study to analyze the effect of job characteristics (X1), compensation (X2) and religiosity (X3) on employee loyalty (Y) Tabassam Farm Mojokerto. Job characteristics have five indicators, namely job skills, task identity, task significance, task autonomy, and task feedback. Compensation has six indicators, namely salary, incentives, bonuses, allowances, insurance, and non- financial rewards. Religiosity has five indicators, namely ideology, practice, experience, knowledge and application. Employee loyalty has four indicators, namely obedience, responsibility, dedication, and integrity. The population of this research is Tabassam Farm employees who have worked for more than two years.This research sample of 73 people. The hypothesis used in this study uses multiple linear regression analysis. The results of this study are job characteristics (X1) and religiosity (X3) have a simultaneous and partial effect on employee loyalty, while the compensation variable (X2) has a simultaneous but not partial effect on employee loyalty. The value of the coefficient of determination in this study is 64.4% which indicates that employee loyalty is influenced by job characteristics, compensation, and religiosity, while the remaining 35.6% is influenced by other variables not examined in this study.